Analisis Kandungan Bunga Telang (Clitoria Ternatea) sebagai Minuman Teh Anti Oksidan - Fitriandita, Adinda Rahma; Damayanti, Duwi Agustina; Rachman, Alief; Ramadhan, Muhammad; Rianto, Saga; Radianto, Denny Oktavina (Sci-tech Journal, 2023)
The terran flower (Clitoria ternatea) is a pigmented plant. Anthocyanins have the potential to be developed as local natural pigments for various foods. Various foods also contain local natural pigments. It improves color quality and is also an antioxidant. Anti-cancer and anti-inflammatory effects. The purpose of this study was to identify the potential of butterfly pea flower extract as a natural antioxidant in food. In this study, the antioxidant activity test was used with the DPPH method. Analyzing the antioxidant capacity and chemical composition contained in butterfly pea extract. The results show that butterfly flower extract can do this used as a source of local natural dyes and natural antioxidants. Added the ability to make various types of food, such as drinks, ice cream, syrup, bread, and biscuits. Keywords: antioxidant, butterfly pea flower, tea drink